2009
DOI: 10.1590/s1676-06032009000300014
|View full text |Cite
|
Sign up to set email alerts
|

Potencial antagônico de Trichoderma spp. originários de diferentes agroecossistemas contra Sclerotinia sclerotiorum e Fusarium solani

Abstract: A partir de 40 amostras de solo, provenientes dos estados do Rio Grande do Sul, Minas Gerais, São Paulo, Bahia, Goiás e Tocantins, uma coleção de 230 isolados monospóricos de Trichoderma spp. foi estabelecida, usando o meio seletivo TSM. Com o objetivo de selecionarem-se isolados com potencial para controle biológico de doenças, foram conduzidos testes de pareamento de culturas em meio BDA, a 20 ºC para Sclerotinia sclerotiorum e a 25 ºC para Fusarium solani f.sp. phaseoli. Antagonismo contra os dois patógenos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 15 publications
1
19
0
10
Order By: Relevance
“…In order to evaluate the antagonistic action of Trichoderma in the control of Fusarium solani, it was observed that 21.74% of the Trichoderma isolates inhibited the growth of the pathogen and 52% had no inhibitory effect against Fusarium in the culture pairing test (LOUZADA et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…In order to evaluate the antagonistic action of Trichoderma in the control of Fusarium solani, it was observed that 21.74% of the Trichoderma isolates inhibited the growth of the pathogen and 52% had no inhibitory effect against Fusarium in the culture pairing test (LOUZADA et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…as a plant growth promoters and numerous researches have been conducted because these fungi produce antimicrobial substances which ensure a wide spectrum of activity against various plant pathogens. Moreover, some strains of Trichoderma promote plant growth by increasing the availability of nutrients and production of growth hormones Louzada et al, 2009). The root colonization often increases the development, crop yield, resistance to abiotic stresses and improves nutrient use (Rubio et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Aproximadamente 80% dos fungos endofíticos produzem compostos biologicamente ativos, como antibióticos, fungicidas e herbicidas [2]. O controle biológico de fitopatógenos tem se apresentado como uma forma promissora e viável, por meio do uso de micro-organismos como agentes protetores de plantas cultivadas [5,6,7]. Desde o início da domesticação das plantas pelos humanos, há 10.000 anos, fitopatógenos têm causado perdas nos campos cultivados e redução do valor estético e do tempo de armazenamento da colheita [8].…”
Section: Introductionunclassified
“…Os testes in vitro apresentam a vantagem de permitir o conhecimento dos mecanismos de ação envolvidos (ex: antibiose e hiperparasitismo) e facilitar a observação das interações entre o antagonista e o fitopatógeno [6,11].…”
Section: Introductionunclassified